A Small Molecule Angiotensin II Type 2 Receptor (AT2R) Antagonist Produces Analgesia in a Rat Model of Neuropathic Pain by Inhibition of p38 Mitogen‐Activated Protein Kinase (MAPK) and p44/p42 MAPK Activation in the Dorsal Root Ganglia. Issue 10 (6th June 2013) - Smith, Maree T.; Woodruff, Trent M.; Wyse, Bruce D.; Muralidharan, Arjun; Walther, Thomas
Abstract Objective There is an unmet clinical need for novel analgesics for neuropathic pain. This study was designed to elucidate the mechanism through which EMA300, a small molecule antagonist of the angiotensin II type 2 receptor (AT2R) with >1, 000‐fold selectivity over the angiotensin II type 1 receptor, produces analgesia in a rodent model of neuropathic pain. Design and Methods Groups of AT2R knockout, hemizygotes, and wild‐type mice with a chronic constriction injury (CCI) of the sciatic nerve received single intraperitoneal (i.p.) bolus doses of EMA300 (100 or 300 mg/kg), and analgesic efficacy was assessed. Groups of control, sham‐operated, and CCI rats were euthanized and perfusion fixed. Lumbar dorsal root ganglia (DRGs) were removed for investigation of the mechanism through which EMA300 alleviates neuropathic pain. Results EMA300 analgesia was abolished in AT2R knockout CCI mice with intermediate responses in the hemizygotes, affirming the AT2R as the target mediating EMA300 analgesia. In CCI rats, DRG immunofluorescence (IF) levels for angiotensin II, the main endogenous ligand of the AT2R, were increased ∼1.5–2.0‐fold (P < 0.05) cf. sham‐controls. Mean DRG IF levels for activated p38 (pp38) and activated p44/p42 (pp44/pp42) MAPK were also increased ∼1.5–2.0‐fold (P < 0.05) cf. sham‐controls. At the time of peak EMA300 analgesia in CCI rats, mean DRG levels of pp38 MAPK and pp44/pp42 MAPK (but not angiotensin II) were reduced to match the respective levels in sham‐controls. Conclusion Augmented angiotensin II/AT2R signaling in the DRGs of CCI rats is attenuated by EMA300 to block p38 MAPK and p44/p42 MAPK activation, a mechanism with clinical validity for alleviating neuropathic pain.